Electric power industry in the conditions of foreign companies exit - D. M. Ovodenko (Вестник университета)
The relevance of the study is due to the fact that there are problems with supply of foreign raw materials and goods to the Russian market for the uninterrupted operation of the energy system as a whole caused by modern complicated economic conditions and current international situation. Besides, there is need to develop and form new conceptual approaches to the strategy of energy systems development amid forced modernisation of the industry. The conducted research is aimed at identifying and analysing existing and new directions in the formation of these original conceptual approaches in conditions of efficient functioning of the Russian industry. Based on the conducted work, the materials of scientists who have studied this problem were examined, and according to the results of the assessment, the following conclusions were formulated. To begin with, non-standard approaches to the management component of the energy systems development within the frame-work of forced modernisation were named. Finally, the potential possibility of rational use of all factors through the synchronisation of processes in diversification production played the role of socio-economic orientation.